Sociology of Literature Approach in the Novel Laut Bercerita by Laila S. Chudori - Fadilah, Lulu Laelatul; Ramadhani, Dzikri; Agus, Cecep (Universitas Pamulang, 2025)
This study employs a sociological approach to analyze Laut Bercerita, a novel by Leila S. Chudori that explores Indonesia’s socio-political struggles during the 1998 Reformation era. The research examines how the novel reflects systemic political oppression, human rights abuses, and the collective resistance of activists against an authoritarian regime. Using a qualitative descriptive method, this study focuses on the experiences of Biru Laut, the central character, whose story highlights the sacrifices made by individuals fighting for democracy, freedom of expression, and justice. Despite facing state-sanctioned violence, including torture and enforced disappearances, the novel illustrates the activists’ persistent struggle against oppression. The findings reveal that Laut Bercerita serves as a medium for social critique, exposing state control mechanisms and their impact on individuals and families of the disappeared. Through its vivid depictions, the novel compels readers to acknowledge the human cost of authoritarian governance. Ultimately, the study emphasizes the role of literature in reflecting societal struggles, fostering historical awareness, and advocating for human rights. By intertwining personal and collective suffering, Laut Bercerita underscores the fragility of freedom and the enduring necessity of resisting authoritarianism